ORBIVIRUS INFECTION IN WHITE-LIPPED PECCARIES (TAYASSU PECARI) FROM MADRE DE DIOS REGION, PERU - Rivera G., Hermelinda (2013)
Peru has 13% of the Amazonian tropical forest which contains over 460 species of mammals, including the white lipped peccary or huangana (Tayassu peccari). This species is of great ecological and commercial importance and a major source of protein for the local inhabitants; however, information about the sanitary situation of this species is scarce. The aim of this study was to determine antibodies against bluetongue virus (BTV) and other Orbivirus in free-living and healthy white lipped peccaries from the Madre de Dios region, Peru. One hundred and six serum samples were evaluated to determine antibodies against BTV by competitive ELISA and other Orbivirus by immunodiffusion agar gel test. Results showed that 7.5% (8/106) of the samples had antibodies against BTV and 29.2% (31/106) against BTV/other Orbivirus. Antibodies against BTV and other Orbivirus were detected in all three localities.